Interactive Flipbook Media to Improve Elementary School Students’ Pancasila Education Learning Outcomes - Ni Putu Julisartini; I Nengah Suastika; Desak Putu Parmiti (Universitas Pendidikan Ganesha, 2026)
Learning carried out by teachers tends to be oriented toward memorization, making it less engaging and less likely to encourage active involvement, resulting in lower learning outcomes. Therefore, this study aims to develop contextually designed interactive flipbooks integrated with digital platforms to improve the learning outcomes of third-grade elementary school students. This type of research is Research and Development (R&D) using the ADDIE model. The subjects of this study were 2 language experts and learning media experts, as well as 10 teachers for practicality testing. The trial subjects were 25 third-grade elementary school students. The data collection method used questionnaires and tests. The research instruments were questionnaire sheets and test questions. The techniques used in analyzing the data were qualitative descriptive analysis, quantitative analysis, and inferential statistics. The study's results, namely the content expert and interactive flipbook expert tests, both showed scores of 1.00, indicating that the material in the interactive flipbook met the Very High Validity criteria. The results of the practicality test by the teacher showed that the average score for all aspects was 95.13 (very practical. The t-test results showed that the use of interactive flipbook media had a significant effect on the learning outcomes of Pancasila Education for grade III elementary school students. It was concluded that Interactive Flipbook Media can improve the Learning Outcomes of Pancasila Education for Elementary School Students.